Household bandwidth and the ‘need for speed’: Evaluating the impact of active queue management for home internet traffic - Kennedy, Jenny; Armitage, Grenville; Thomas, Julian (Journal of Telecommunications and the Digital Economy, 2017)
In this paper, we aim to contribute to the policy debate on bandwidth needs by considering more closely what happens in household networks. We draw upon both social and technical studies modelling household applications and their uses to show how queue management protocols impact bandwidth needs. We stress the impact of internet traffic streams interfering with each other, and describe three different categories of internet traffic. We demonstrate how the use of active queue management can reduce bandwidth demands. In doing so we consider how, and to what degree, household internet connections are a constraint on internet use. We show that speed demand predictions are skewed by a perceived need to protect the Quality of Service experienced by latency-sensitive services when using current gateway technologies.